Kitchen dance - Manning, Maurie (New York : Scholastic, 2008)
Two sleepy children sneak out of their beds to watch as their parents, who love each other very much, break into a dance while washing the dishes.
K
b
b
Keywords: Bedtime -- Fiction; Family life -- Fiction; Hispanic Americans -- Fiction